2021
DOI: 10.1111/hequ.12307
|View full text |Cite
|
Sign up to set email alerts
|

Using network DEA to inform policy: The case of the teaching quality of higher education in England

Abstract: Current literature on higher education (HE) performance only considers the production of graduates and not graduate employment. The latter needs to be factored into the HE production model as it not only measures the true impact of HE institutions (HEIs), but also provides policy implications on how resources should be allocated. Furthermore,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Several studies have discussed the measurement of teaching performance of educators’ techniques and strategies. Teaching performance may be evaluated through students’ opinions ( Rahimi et al, 2012 ), educators’ perception ( Kaldi, 2009 ), graduate employability ( Yorke and Knight, 2004 ; Yorke, 2006 ; Lee and Johnes, 2021 ) and assessment of learners’ acquired knowledge ( Ahmed et al, 2015 ; Al-Jubari et al, 2019 ). It has also been found that educators are evaluated based on their research skills in addition to extensive professional experience as their research skills can enhance the classroom experience as well ( Romero and Bobkina, 2021 ; Suyo-Vega et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have discussed the measurement of teaching performance of educators’ techniques and strategies. Teaching performance may be evaluated through students’ opinions ( Rahimi et al, 2012 ), educators’ perception ( Kaldi, 2009 ), graduate employability ( Yorke and Knight, 2004 ; Yorke, 2006 ; Lee and Johnes, 2021 ) and assessment of learners’ acquired knowledge ( Ahmed et al, 2015 ; Al-Jubari et al, 2019 ). It has also been found that educators are evaluated based on their research skills in addition to extensive professional experience as their research skills can enhance the classroom experience as well ( Romero and Bobkina, 2021 ; Suyo-Vega et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…DEA is one of the most common methods used to measure HEI efficiency (Monaco, 2012; Wolszczak-Derlacz, 2017; Salas-Velasco, 2020; Lee and Johnes, 2021; Tavares et al , 2021; Thai and Noguchi, 2021; Herberholz and Wigger, 2021). A two-step DEA was developed to conduct a comparative analysis of the efficiency of 23 Portuguese public HEIs.…”
Section: Influencers Of Higher Education Institutions Efficiency and ...mentioning
confidence: 99%
“…The papers in [87][88][89] consider organizations of the higher education sector as DMU and divide their activity into two stages: education and scientific research. In [89], educational activities divided into two sub-processes: the process of the undergraduate level and the graduate level.…”
Section: Fund Transfer Incomementioning
confidence: 99%